On the role of a permeable groyne in beach morphodynamics during sea-breeze events in Yucatàn, Mexico - Hofman, Anne; Roos, Pieter; Torres-Freyermuth, Alec (Student Undergraduate Research E-journal!, 2017)
The north coast of the Yucatàn peninsula in Mexico is vulnerable to strong sea breezes, which in turn causes high waves, driving high rates of erosion due to littoral transport. To find a solution for erosion problems caused by currently applied measurements, a permeable groyne was introduced, tested and monitored during a 24h experiment. Concluded was that the permeable groyne has the potential to reduce downdrift erosion problems due to its permeability. However, long term effects could not be properly assessed and requires a follow-up study.